APDH and IHRDA v Mali: recent developments in the jurisprudence of the African Court on Human and Peoples' Rights. Issue 5 (27th May 2020) - Capone, Francesca
ABSTRACT: The present article aims at providing an overview of the new developments in the jurisprudence of the African Court on Human and People's Rights (ACtHPR). In particular this article will focus on two important aspects that have been recently addressed in the case of APDH and IHRDA v Mali, namely the ever-expanding breadth of the Court's material jurisdiction and the bolder implementation of its remedial power. It is argued that the approach adopted by the ACtHPR in relation to these two aspects departs from the previous case law and offers fresh insights into the progress made by the youngest regional human rights court over a very short amount of time.